Pengaruh Debt Equity Ratio, Return On Assets, Company Size, dan Audit Committee Terhadap Tax Avoidance pada Perusahaan Sektor Properti dan Real Estat yang Terdaftar di Bursa Efek Indonesia - Pertiwi, Amali (Jurnal Keuangan dan Perbankan Syariah, 2024)
This study aimed to examine the impact of independent variables, including Debt Equity Ratio (DER), Return on Assets (ROA), company size, and audit committee, on the dependent variable, tax avoidance. The population consisted of 84 companies in the property and real estate sector listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. Purposive sampling was used in the sample selection process, yielding a sample of 63companies. Employing a quantitative approach, the research employed quantitative descriptive analysis, specifically multiple linear regression analysis. Findings indicate that Debt Equity Ratio positively influences tax avoidance, while Return on Assets and company size have a negative effect. Additionally, the audit committee does not impact tax avoidance.